2018
DOI: 10.1128/aem.01423-18
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antimicrobial Peptide GH12 on the Cariogenic Properties and Composition of a Cariogenic Multispecies Biofilm

Abstract: Dental caries is a biofilm-mediated disease that occurs when acidogenic/aciduric bacteria obtain an ecological advantage over commensal species. In previous studies, the effects of the antimicrobial peptide GH12 on planktonic bacteria and monospecies biofilms were confirmed. The objectives of this study were to investigate the effects of GH12 on a cariogenic multispecies biofilm and to preliminarily explain the mechanism. In this biofilm model, Streptococcus mutans ATCC 70061 was the representative of cariogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 62 publications
3
25
0
Order By: Relevance
“…In agreement with previous studies, GH12 exhibits αhelix conformations in solvents mimicking interactions at the membranes [76]. Our results are in agreement with the trends that are shared by the modified GH12 and GH12-M2.…”
Section: Effect Of Peptide Conformation On Functionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with previous studies, GH12 exhibits αhelix conformations in solvents mimicking interactions at the membranes [76]. Our results are in agreement with the trends that are shared by the modified GH12 and GH12-M2.…”
Section: Effect Of Peptide Conformation On Functionsupporting
confidence: 93%
“…We further explored the likely residues involved in forming helical secondary structure through computational structure flexibility. The α-helix secondary structure of GH12 is a design target for functional integration of the peptide to the adhesive system [76]. The presence of α-helix conformation was confirmed through our vibrational spectroscopy measurements for peptides including the modified GH12.…”
Section: Vibrational Spectroscopysupporting
confidence: 56%
See 1 more Smart Citation
“…Even at a sub‐inhibitory dose of 0.5 × MIC, GH12 inhibited acid production, EPS synthesis and biofilm formation of S. mutans and significantly down‐regulated the expression of virulence genes including ldh, gtfBCD, vicR, liaR and comDE (Wang, Wang, et al, ). Subsequently, Jiang et al () showed that treatment of a three species biofilm comprising S. mutans, S. gordonii and S. sanguinis with 8 µg/ml GH12 reduced the abundance of S. mutans and reduced the level of water‐insoluble glucan (Jiang et al, ). Interestingly, as the abundance of S. mutans decreased in the treated biofilms, the level of S. gordonii increased and became the dominant organism in the biofilm by 48 hr.…”
Section: Antimicrobial Peptide‐based Mimeticsmentioning
confidence: 99%
“…The good biocompatibility of GH12 in vivo was further confirmed in a rat model (Wang et al 2019). Furthermore, GH12 was reported to have excellent antimicrobial properties against dental cariogenic bacteria and biofilms in vitro , especially for Gram‐positive bacteria (Tu et al 2016, Wang et al 2017, Jiang et al 2018). GH12 has been reported to have rapid and efficient bactericidal activity against oral Streptococci , Lactobacilli and Actinomyces species with low concentrations (8.0–64.0 mg L −1 ) (Tu et al 2016).…”
Section: Introductionmentioning
confidence: 99%